Preparation And Properties Of Low Density Polyethylene (LDPE) / Thermoplastic Sago Starch (TPSS) / Kenaf Composites - Majid, Rohani Abdul (2010)
In this research, thermoplastic sago starch (TPSS) was incorporated in low density polyethylene (LDPE). TPSS loadings were varied from 10 to 50 wt. % to study the effect of adding TPSS on tensile properties, morphology, water absorption, natural weathering and soil burial properties of LDPE/TPSS blends. Polyethylene grafted maleic anhydride (PE-g-MA) was added into the second series of blends to study the effect of the addition of compatibilizer to the properties of the blends. For the third series, kenaf fiber was incorporated in the blends to study the effect of the addition of natural fiber. Kenaf fiber loading was varied from 5 to 40 wt. % to determine the optimum kenaf fiber loading in the LDPE/TPSS/Kenaf composites.